OPTIMALISASI PERAN GURU SMA/SEDERAJAT DALAM KURIKULUM PENDIDIKAN PAJAK DI ERA SOCIETY 5.0 - Lutfiya Tussifah; Hapsari, Annisa Diah (JURNAL PAJAK INDONESIA, 2025)
The government's efforts to increase tax awareness need to be accelerated in the aspect of tax education for students at Senior High School level through the tax curriculum. However, the focus of tax education has been limited to the internalization of tax education for students and has little attention in the transfer of tax knowledge to teachers. This research uses qualitative methods through literature studies which examines the efforts that have been made by DJP in empowering teachers at Senior High School education level to implement tax inclusion in education as well as provide alternative policies for empowering Senior High School teachers in the education curriculum at the era of society 5.0. We propose a tax inclusion strategy for teachers in the form of tax training for teachers, use of applications for tax reporting simulations, and discussion platforms for teachers and students related to taxation.